Transformation Of Islamic Education: Maintaining Local Wisdom Values In The Digital Era - Fahmi Dina Maula Bahari; Sugiono (Al-Qalam Institue, 2025)
The digital transformation in Islamic boarding schools (pesantren) has become an essential aspect of modernizing da’wah (Islamic preaching) while maintaining traditional values. This research examines how Nurul Jadid Islamic Boarding School has integrated digital platforms such as YouTube, Instagram, and its official website to disseminate Islamic teachings and engage with a wider audience. The study aims to explore how digital da’wah can be effectively implemented without compromising local wisdom and Islamic principles. A qualitative case study approach was used, employing in-depth interviews, non-participatory observation, and documentation of digital content. The findings reveal that Nurul Jadid has successfully embraced digital tools for preaching while preserving cultural and religious identity, with active student involvement as content creators under the supervision of kyai (Islamic scholars). Despite challenges such as limited resources and infrastructure, the school has adapted well to digital communication. The study contributes to the literature by highlighting the balance between innovation and tradition in digital da’wah and offers a model for other pesantren to navigate similar transformations.